Sistem Pendukung Keputusan Metode AHP Pemilihan Siswa Akademik Terbaik pada SMP Dharma Bakti Jakarta Timur - Winton Almundarisna; Aan Risdiana; Achmad Birowo (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
In the era of increasingly advanced technological development, decision support systems (DSS) play an important role in improving the quality of decision-making in the education sector. The selection staff at SMP Dharma Bakti find it difficult to objectively determine the best academic students because they still use a manual method that is prone to errors. This research aims to design a web-based decision support system that can help selection staff assess and determine their best academic students objectively and quickly. This system is developed using the PHP programming language, MySQL database, LARAVEL 8 framework, and applies the Analytical Hierarchy Process (AHP) method within it. This research produces a system that allows the SMP Dharma Bakti Selection Officers to input alternative data, namely student data, determine the weight of criteria and sub-criteria, and view the ranking results automatically, thus greatly facilitating the SMP Dharma Bakti Selection Officers in determining their best academic students.